Acute hemorrhagic and necrotizing pneumonia, splenitis, and dermatitis in a pet rabbit caused by a novel herpesvirus (leporid herpesvirus-4) - Brash, Marina L. (Canadian Veterinary Medical Association, 2010)
A 1.5-year-old female rabbit (doe) was presented with a 3-day history of lethargy, anorexia, and mild facial swelling. The animal died shortly after examination and severe, acute hemorrhagic pneumonia was noted grossly. An alphaherpesvirus consistent with leporid herpesvirus-4 was isolated and characterized from this animal. This is the first confirmed report of the disease in Canada.